2010
DOI: 10.1177/0741713610380448
|View full text |Cite
|
Sign up to set email alerts
|

Community in Cyberspace: Gender, Social Movement Learning, and the Internet

Abstract: Feminist nonprofit organizations are sites of informal and nonformal learning where citizens learn advocacy, literacy, and the practices of social democracy. With the growing use of information and communication technologies in the nonprofit sector, there are questions as to how well organizations are able to make use of this technology to further their goals of promoting social movement learning and activism. This article reports on a systematic analysis of 100 websites for feminist organizations in Canada. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
(28 reference statements)
0
22
0
1
Order By: Relevance
“…Russell described SeniorNet as an example of an online learning community emphasizing "collective and participatory communication . Irving and English (2011) noted that there were "innumerable missed opportunities for feminist organizations to share knowledge and engage in community-based learning" (p. 274). .…”
Section: Online Communitiesmentioning
confidence: 99%
“…Russell described SeniorNet as an example of an online learning community emphasizing "collective and participatory communication . Irving and English (2011) noted that there were "innumerable missed opportunities for feminist organizations to share knowledge and engage in community-based learning" (p. 274). .…”
Section: Online Communitiesmentioning
confidence: 99%
“…However, certain studies have shown how some movements, like feminist organizations, promote opportunities and spaces for non-formal learning (workshops, short courses) and informal (day-to-day) learning using new digital media and technologies. Through these spaces, movements offer mentoring services or support to women who are victims of all kinds of violence, including sexual abuse (Irving & English 2011). In the same way, environmental organizations promote education on sustainability through videos and social networks.…”
Section: Activism and Its Relationship With The Field Of Educationmentioning
confidence: 99%
“…In terms of international adult education, Irving and English (2011) examined social movement learning in feminist organizations in Canada through the use of information technology and LeNoue, Hall, and Eighmy (2011) and social media in the service of self-directed learning. In terms of international adult education, Irving and English (2011) examined social movement learning in feminist organizations in Canada through the use of information technology and LeNoue, Hall, and Eighmy (2011) and social media in the service of self-directed learning.…”
Section: Literature Reviewmentioning
confidence: 99%